L’impact de l’ouverture de la brèche dans la langue de Barbarie à Saint-Louis du Sénégal en 2003 : un changement de nature de l’aléa inondation ? - Paul Durand (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
The French colonial city of Saint-Louis du Senegal, declared as World Heritage by UNESCO, is built on a sandbank island in the estuary of the Senegal River (west coast of Africa). On the west side of Saint-Louis, a long and narrow sandspit, the Barbary Tongue (Langue de Barbarie), protects the town from marine submersions. Until the end of 2003, the island of Saint-Louis was located approximately thirty kilometers upstream from the river’s mouth. Therefore, the town was subjected to recurring flood events, often occurring towards the end of the rainy season, due to low discharge conditions of river water into the ocean. To reduce the problem, a breach was opened in the Barbary Tongue in early October 2003, about 7 km southward from the city. After a few months, the gap has widened dramatically and there is now a considerable increase in marine influence in the hydrological regime. The aim of our study is to analyze consequences of such event on flood hazards evolution, knowing that Saint-Louis has not experienced further significant flooding, river waters being rapidly drains off during flood events. As the city of Saint-Louis is lying slightly above the level of actual high seas, it might be vulnerable to rising sea level, even moderate. In this context, we try to discuss what could be the consequences of sea level rise on the city, if marine influence should persist in the regime of Senegal river in the years to come. A model was developed to simulate flood propagation in the city for various scenarios, made from estimates of rising sea level by the end of the century (IPCC, 2007; Rahmstorf et al, 2007; Grinsted et al, 2009). It shows that the town of Saint-Louis could be flooded during the highest annual water during the 21st century.